2018
DOI: 10.1038/s41593-017-0047-3
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 pathology disrupts nuclear pore complexes and nucleocytoplasmic transport in ALS/FTD

Abstract: The cytoplasmic mislocalization and aggregation of TAR DNA-binding protein-43 (TDP-43) is a common histopathological hallmark of the amyotrophic lateral sclerosis and frontotemporal dementia disease spectrum (ALS/FTD). However, the composition of aggregates and their contribution to the disease process remain unknown. Here, we used proximity-dependent biotin identification (BioID) to interrogate the interactome of detergent-insoluble TDP-43 aggregates, and found them enriched for components of the nuclear pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
426
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 466 publications
(481 citation statements)
references
References 63 publications
34
426
1
Order By: Relevance
“…The nuclear shape was slightly abnormal in both C9orf72 and non-hereditary ALS cases. This is consistent with a parallel study showing that nuclear pore defects are not unique for C9orf72 cases but are also directly connected to the TDP-43 pathology in ALS [4].…”
supporting
confidence: 80%
“…The nuclear shape was slightly abnormal in both C9orf72 and non-hereditary ALS cases. This is consistent with a parallel study showing that nuclear pore defects are not unique for C9orf72 cases but are also directly connected to the TDP-43 pathology in ALS [4].…”
supporting
confidence: 80%
“…Since TDP-43 pathology has been attributed to nuclear membrane defects and problems with nucleocytoplasmic transport system [13, 35], we first investigated the nuclear membrane of Betz cells in both control and TDP-43 cases. Nuclear membranes of Betz cells in normal controls were almost perfect circle and no defects were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TDP-43 directly regulates RanGap1 and depletion of TDP-43 results in downregulation of RanGap1 [71]. Transportin 1 does not directly bind to TDP-43 [45] but TDP-43 aggregates sequester Transportin 1 in the cytoplasm of cortical neurons contributing to nucleo-cytoplasmic transport defects [13]. It has also been suggested that depletion of TDP-43 results in elevated levels of Transportin 1 [63].…”
Section: Discussionmentioning
confidence: 99%
“…iPSC-derived neurons from patients with C9orf72 -ALS show evidence of nucleocytoplasmic defects, with decreased nuclear/cytoplasmic Ran ratio [170] and decreased nuclear RCC1/RanGEF [60], as well as large RanGAP1-positive puncta that occasionally co-localize with RNA foci [170]. In addition, TDP-43 inclusions in HeLa cells may sequester proteins involved in nucleocytoplasmic transport [17], and knockdown of TDP-43 in cell models leads to altered expression of a large group of proteins regulated by TDP-43, including nucleocytoplasmic transport proteins [112, 136]. …”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%